Watching Together the Film ‘Miracle in Cell No. 7’: Building Empathy and Togetherness - Nadia Fahma Kamila; Ettik Arifah; Fatah Abdul Hakim; Nihayatun Nisa; Puji Lestari (Universitas Palangka Raya, 2024)
The activity of watching the film ‘Miracle in Cell No. 7’ together with children aims to build empathy and togetherness among participants. This film, which tells the emotional relationship between a father and his child amidst significant challenges, offers profound humanitarian values. The methodology used includes organizing the event in the RT 08 RW 01 area, where children are invited to watch the film together, followed by an interactive discussion about the themes presented in the film. The results of this activity indicate an increase in children's understanding of the importance of empathy and cooperation, as well as creating a positive atmosphere of togetherness. This activity is expected to serve as a model for similar programs in the future, in an effort to strengthen social values among the younger generation.